Perbandingan Skor Prediksi dalam Pembelajaran Mesin pada Keselamatan Penumpang Kapal: Comparison of Prediction Scores in Machine Learning on Ship Passenger Safety - Perkasa, Mochamad Althaf Pramasetya; Rahmatulloh, Alam (Jurnal Mahasiswa Teknik Informatika, 2024)
Passenger safety is an important aspect of the shipping industry, and precise predictions of emergencies and safety situations can provide great advantages in managing risks at sea. Precise prediction of emergency and safety situations can provide great advantages in managing risks at sea. This research involves collecting and analyzing historical data on ship accident incidents and their influencing factors. Machine learning methods, such as logistic regression, KNN, Naïve Bayes Classifier, Decision Tree, Random Forest, etc. will be used to identify patterns in the data that can be used to predict ship passenger safety. The data used in this study includes variables such as weather, ship state, number of passengers, and other relevant factors. The research data was taken from titanic passengers. The results of this study resulted in a model that is suitable for predicting the safety of ship passengers, namely the random forest model and decision tree getting the highest score compared to other models, the prediction score is 84.29%.